Revision of the Lemonia taraxaci complex, with a description of a new species from Italy and clarification of the status of Lemonia strigata (Lepidoptera: Brahmaeidae: Lemoniinae) - Prozorov, Alexey M.; Prozorova, Tatiana A.; Volkova, Julia S.; Yakovlev, Roman V.; Nedoshivina, Svetlana V.; Pinzari, Manuela; Pinzari, Mario; Scalercio, Stefano; Bianco, Giovanni; Saldaitis, Aidas; Hausmann, Axel; Revay, Edita E.; et al. (Zootaxa)
The species Lemonia taraxaci (Denis & Schiffermuller, 1755) is divided into three species based on distribution areas and cytochrome c oxidase subunit 1 (COI) distances above 2%: Central European Lemonia taraxaci (type locality: Austria, Vienna area), Eastern European to South Siberian Lemonia sibirica Wnukowsky, 1934 stat. rev., bona sp. (type locality: Russia, Novosibirsk Oblast, Ozero-Karachi and Russia, Altai Krai, Kornilovo), and Italian Lemonia italiana sp. n. (type locality: Italy, Calabria centr., Sila grd., Casali del Manco, San Nicola Silano (CS)). Authorship of Lemonia strigata Antoshin & Zolotuhin, 2011 is reconsidered. The close relation between the typical L. strigata and taraxaci-like adults from the Balkans is proven genetically. According to this, L. strigata is suggested to be a junior synonym of taraxaci- looking Lemonia taraxaci var. montana Buresch, 1915 (type locality: Bulgaria, Rhodope Mts, Musala), although further DNA investigation is needed to prove this hypothesis.